Lucilia silvarum Meigen (Diptera: Calliphoridae) Is a Primary Colonizer of Domestic Cats (Felis catus) - Kelly Bagsby; Krystal Hans (Insects, 2024)
Lucilia silvarum Meigen (Diptera: Calliphoridae) is widespread throughout North America and Europe. Described in 1826, this blow fly was quickly associated with myiasis in amphibians, and to date has rarely been reported in carrion. There is limited data regarding the time of colonization of animals with fur and the interpretation of this data is difficult due to variation in the animal models used. During an examination of initial insect colonization of cats (Felis catus) with light and dark fur, twelve domestic short-haired cats were placed in cages 15.2 m apart in a grassy field in West Lafayette, Indiana, USA. Eggs from initial oviposition events were collected and reared to identify the colonizing species. Three species of Lucilia (Diptera: Calliphoridae), including L. silvarum, colonized the cats on the initial day of placement. In this study, L. silvarum was the primary colonizer of cats, and this may be the first study where a large number of L. silvarum were collected. Further studies should include development studies on L. silvarum to understand its life history and aid in time of colonization estimations. More work regarding the colonization of furred mammals is needed to further examine L. silvarum as a primary colonizer.